Exordio a la memoria colectiva y el olvido social - Mendoza García, Jorge (Athenea Digital, 2005)
This article argues that memory and forgetting, far from being the individual matters they were taken to be in the 20th century, are social phenomena: that they are collective, or social, products, and form two sides of the same coin. Collective memory has its own resources:it is guided by societal forces and sustained by language. Social forgetting, on the other hand, is sustained by silence, oppression and censorship. The two together furnish society with its presences and its absences. There is a conflict between memory and oblivion. Where one flourishes, the other withers, and vice versa. Societies are built on just such problematic relationships.